Is serum creatinine mandatory prior to contrast ehanced computer tomography - Adhikari, Deepak; Gautam, Rupesh; Moktan, Sweta; Mallik, Mukesh; Sakhakarmi, Mamita (Journal of Chitwan Medical College, 2018)
Introduction: Contrast-enhanced Computed Tomography (CECT) is an imaging technique to diagnose many clinical manifestations. Contrast media used in CECT can lead to contrast induced nephropathy (CIN). Hence, screening of serum creatinine (SCr) level prior to CECT is commonly practiced as it is considered to be an indicator for the risk of Contrast Induced Nephropathy (CIN). But, it adds up extra cost and also increases duration for investigation. The purpose of this study is to find out, if SCr screening can be skipped among certain group by medical history related to risk factors of CIN. Methodology: A total 250 patient SCr were obtained prior to CECT over period of 4 months between June 2016 to September 2016. Duplication in the samples was avoided. A survey of medical history regarding risk factors for CIN was taken in each case. Chi square test and odds ratio was applied for data analysis. Results: In this study 68% of total (250) patients were found to have normal SCr level without any risk factors for CIN and among 3% abnormal categorized patients (SCr ≥1.5mg/dl)) 71% (5 of 7) were identified with risk factors. Conclusions: The data suggests that screening SCr prior to CECT is significant only to those patients who acquire any of the identifiable risk factors for CIN. Those patients who are not identified with any of the associated risk factors, especially for renal disease, are not mandatory to obtain SCr value. This can reduce many challenges while checking patient’s creatinine status, such as patient’s booking delays, extra cost and time, additional pricking while taking blood sample. This practice can also increase the departmental throughput and efficiency of service.